Analisis panjang bidang kontak perontokan lada pada mesin perontok lada tipe silinder berjaring - Leo Dedy Anjiu; Suhendra Suhendra; Ari Rianto (Universitas Muhammadiyah Metro, 2023)
The threshing process is one of the problems because currently is still mostly done manually. The development of a mechanical pepper threshing system has been carried out by making a pepper threshing machine. Further development is carried out by analyzing the mechanism of pepper threshing. Based on these problems, a research was conducted to analyze the length of the threshing contact area on the pepper threshing mechanism. The independent variable of the research is the length of the threshing contact area. The dependent variables were threshing capacity, threshing efficiency and damage percentage of pepper. The length of the threshing contact area was varied namely 2, 4, 6 and 8 cm. The threshing mechanism rotational speed used is 360 rpm. The tensile strength of the spring on the threshing net is 0,22 kg/cm. The amount of pepper processed in 1 test is 0,4 kg. Based on the test result, the length of the threshing contact area is inversely proportional to the threshing capacity, and directly proportional to the treshing efficiency and the percentage of damage. The highest capacity and the smallest damage percentage were obtained at a contact area length of 2 cm, respectively 109,09 kg/hour and 10,85%. The highest threshing efficiency was obtained at a contact area length of 8 cm is 95,09%.